2017
DOI: 10.1002/evl3.34
|View full text |Cite
|
Sign up to set email alerts
|

Egg chemoattractants moderate intraspecific sperm competition

Abstract: Interactions among eggs and sperm are often assumed to generate intraspecific variation in reproductive fitness, but the specific gamete‐level mechanisms underlying competitive fertilization success remain elusive in most species. Sperm chemotaxis–the attraction of sperm by egg‐derived chemicals—is a ubiquitous form of gamete signaling, occurring throughout the animal and plant kingdoms. The chemical cues released by eggs are known to act at the interspecific level (e.g., facilitating species recognition), but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 76 publications
2
73
1
Order By: Relevance
“…Instead, the fitness consequences of OA will depend on whether the observed effect disrupts the capacity of eggs to promote fertilizations by preferred sperm. In M. galloprovincialis, females use ECs to differentially regulate sperm movement and physiology (Evans et al, 2012;Kekäläinen & Evans, 2016;Oliver & Evans, 2014)-processes that ultimately favor sperm from genetically compatible males when multiple ejaculates compete for fertilization (as is likely in realistic mass spawning events) (Lymbery et al, 2017). This form of gamete-mediated mate choice provides benefits to females in terms of enhanced offspring viability (Oliver & Evans, 2014 Kekäläinen, Larma, Linden, & Evans, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the fitness consequences of OA will depend on whether the observed effect disrupts the capacity of eggs to promote fertilizations by preferred sperm. In M. galloprovincialis, females use ECs to differentially regulate sperm movement and physiology (Evans et al, 2012;Kekäläinen & Evans, 2016;Oliver & Evans, 2014)-processes that ultimately favor sperm from genetically compatible males when multiple ejaculates compete for fertilization (as is likely in realistic mass spawning events) (Lymbery et al, 2017). This form of gamete-mediated mate choice provides benefits to females in terms of enhanced offspring viability (Oliver & Evans, 2014 Kekäläinen, Larma, Linden, & Evans, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that, among intraspecific male–female pairings, ECs differentially moderate patterns of sperm attraction (Evans, García‐González, Almbro, Robinson, & Fitzpatrick, ), swimming behavior (Oliver & Evans, ), and changes to sperm surface physiology (e.g., acrosome reaction and arrangement of glycan molecules; Kekäläinen & Evans, ). These effects of ECs on sperm behavior and physiology are likely to explain how females regulate fertilization in favor of genetically compatible males when ejaculates from different males compete (Lymbery, Kennington, & Evans, ). However, whether OA alters these prefertilization processes has not yet been tested.…”
Section: Introductionmentioning
confidence: 99%
“…We set up a series of 2 × 2 factorial crosses (n = 11), each involving two randomly selected females and males that were crossed in all four combinations (Table S2). This enabled us to evaluate the importance of interacting male-by-female effects, which would be consistent with cryptic female choice favouring specific males, mediated by substances in the female's cues (Evans, Garcia-Gonzalez, Almbro, Robinson, & Fitzpatrick, 2012;Lymbery et al, 2017;Poli et al, 2019;Rosengrave et al, 2008). Males and females were housed in separate holding tanks, and no attention was paid to body size during retrieval from the holding tanks.…”
Section: Gamete Donor Identity Experimental Designmentioning
confidence: 99%
“…However, emerging evidence from several taxa confirms that even with limited or no control over mating partners, females are able to exert considerable influence over fertilization using post-ejaculatory mechanisms of gamete selection (reviewed in Kekäläinen & Evans, 2018). For example, mytilid mussels have egg-derived chemical signals that can differentially bias competitive fertilization success towards genetically compatible male gametes (Lymbery, Kennington, & Evans, 2017). Similarly, the ovarian fluid of female ocellated wrasse (Symphodus ocellatus) changes the outcome of sperm competition by favouring males with preferred phenotypes who produce fewer but higher-quality sperm in sperm competition (Alonzo, Stiver, & Marsh-Rollo, 2016).…”
mentioning
confidence: 99%
“…The sperm-attracting substances secreted by female genital tract are called chemoattractant. After binding with specific sperm surface receptors, chemoattractant activates downstream pathways, increase the intracellular cAMP concentration and Ca 2+ influx, and accelerate sperm motility (Blengini et al, 2011; Lymbery et al, 2017). CXCL12 is a unique chemoattractant and plays an important role in the growth, metastasis and invasion of tumour cells (Esencay et al, 2013; Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%